2023
DOI: 10.1007/s10072-023-06624-z
|View full text |Cite
|
Sign up to set email alerts
|

The imbalance between Bregs, Tfh, and Tregs in patients with anti-N-methyl-D-aspartate receptor encephalitis

Abstract: Objective To detect the alteration of regulatory B cells (Bregs), follicular helper T cells (Tfh), and regulatory T cells (Tregs) frequencies in patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis. Analyze their association with clinical severity and activity, and explore the effects of different immunotherapies on those immune cell subsets. Methods We enrolled 21 patients with anti-NMDAR encephalitis, 22 patients with neuromyelitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Blocking the interactions may also be a treatment strategy for AE. Li et al observed a significant decrease in the expression of regulatory B cells (Bregs) and regulatory T cells (Tregs) and an increase in T follicular helper cells (Tfh) in patients with NMDAR AE, indicating that Bregs may also be involved in AE pathogenesis (51). Bregs do not have a distinctive transcription factor and are characterized by the production of the inhibitory cytokine IL-10.…”
Section: Current Status and Prospects Of B-cell Targeted Therapymentioning
confidence: 99%
“…Blocking the interactions may also be a treatment strategy for AE. Li et al observed a significant decrease in the expression of regulatory B cells (Bregs) and regulatory T cells (Tregs) and an increase in T follicular helper cells (Tfh) in patients with NMDAR AE, indicating that Bregs may also be involved in AE pathogenesis (51). Bregs do not have a distinctive transcription factor and are characterized by the production of the inhibitory cytokine IL-10.…”
Section: Current Status and Prospects Of B-cell Targeted Therapymentioning
confidence: 99%
“…5 In related studies in the field of aquatic feeds, the use of plant protein sources like soybean meal, cottonseed meal, singlecelled algae and soybean protein concentrate can replace FM in some aquatic animal feeds to some extent and will not have negative effects on aquatic animals' growth, feed utilization, nutritional quality and immunity. [6][7][8][9] However, there are many problems with plant protein raw materials, for example, containing different kinds of antinutritional factors, high fiber content, amino acid imbalance, and its replacement of FM ratio above a certain level will affect the growth and health of aquatic animals to varying degrees, especially for carnivorous fish. 10,11 And the increased use of plant protein raw materials will lead to increased competition between feed production and human food supply.…”
Section: Introductionmentioning
confidence: 99%